The Relationship Between Ethnic Diversity And Innovation At Manufacturing X (Malaysia) - Ooi , Peng Hong (2010)

(untitled)
Salah satu faktor terpenting untuk kejayaan and perkembangan organisasi adalah kapasiti untuk menjadi inovatif. Kebelakangan ini, jurang inovasi di Manufacturing X (Malaysia) semakin dirasai dengan penurunan kuantiti dan kualiti idea-idea inovatif dari para pekerjanya. Pihak pengurusan atasan organisasi ini percaya bahawa para pekerja dari pelbagai etnik adalah kunci kejayaannya sebagai pemimpin inovatif dalam teknologi. Justeru itu, diversiti etnik dijadikan suatu strategi untuk meningkatkan tahap inovasi. Kajian ini bertujuan menyelidiki hubllngan diversiti etnik dan inovasi di Manufacturing X (Malaysia). Kajian ini juga melihat samada konflik dalam kumpulan (yang terdiri daripada konflik perhubungan, tugas, dan proses) berfungsi sebagai perantaraan di dalam hubungan diversiti etnik dan inovasi, seperti yang dicadangkan oleh kajian-kajian sebelumnya. Selaras dengan kajiankajian terdahulu, diversiti etnik didapati mempunyai hubungan positif dengan inovasi. Walau bagaimanapun, hanya· peratusan yang sangat kecil dalam perubahan inovasi disebabkan oleh perubahan dalam diversiti etnik. The capacity to be innovative has been underlined as one of the most important factors for organizational survival and grmvth. At Manufacturing X (Malaysi~), innovation gap is profound as measured by the reducing quantity and quality of innovative ideas submitted by employees over the past few years. The top management believes that a workforce consists of different ethnicities is the key to its success as an innovative leader in technology, and uses it as a strategy to enhance innovation. This study investigates the relationship between ethnic diversity and innovation at Manufacturing X (Malaysia). The literature review suggests that' ethnic diversity and innovation may not be a direct relationship and intra-group conflict may be a mediator in the relationship. Hence, intra-group which consists of relationship, task, and process conflict, is included in the study to see if it mediates the ethnic diversity and innovation relationship. Consistent with prior studies, ethnic diversity is found to have a positive relationship with innovation. However, only a very small percentage of the variation in innovation is explained by the variation in ethnic diversity.